Minat Nasabah pada Produk Tabungan iB Hasanah (Studi Kasus di Bank BSI Ex BNI Syariah Kantor Cabang Mataram) - Siti Ahdina Saadatirrohmi; Baiq Riyana (Universitas Islam Negeri Mataram, 2022)
This study aims to analyze customer interest in the iB Hasanah savings product (a case study at BSI Bank ex BNI Syariah Mataram Branch Office). This research uses descriptive qualitative method. Data collection from the informants was carried out using interview, observation, and documentation techniques. The results showed that customer interest in iB Hasanah savings was influenced by marketing mix factors. The marketing mix factor that becomes the dominant influence is related to product and price, where the iB Hasanah savings account has four things that make customers interested in using it, namely: provisions for small initial deposit balances, no monthly administration fees, ATM balances up to zero rupiah and fast withdrawals. can be done at any time.